2017
DOI: 10.1017/jfm.2017.674
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of high speed wind tunnel flow disturbance measurements using stagnation point probes

Abstract: Since supersonic test facilities have tunnel noise that strongly influences boundary layer transition experiments, the determination of tunnel noise is of great significance to properly evaluate and interpret experimental results. The composition of tunnel noise, which consists of acoustic, entropy and vorticity modes, highly influences the boundary layer receptivity. The measurement of the separate modes is a major goal of ongoing research. In this study, the properties of stagnation point probes for a newly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…A new modal decomposition method was proposed to decompose hot-wire and pitot-probe measurements of freestream disturbances into the three Kovasznay modes (i.e., acoustic, entropy, and vorticity modes). By replacing the pitot-probe transfer function by Stainback and Wagner [33] with the DNS-predicted pitot-probe transfer function by Schilden and Schröder [40], the new combined modal decomposition method can yield rms values of modal amplitudes within a selected frequency band. In all, the joint effort of the specialists group has resulted in a significantly improved knowledge base pertaining to the nature and spectral contents of windtunnel freestream disturbances, with the purpose of quantifying the stochastic input to the receptivity process in a broadband disturbance environment of conventional, cold-flow hypersonic wind tunnels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A new modal decomposition method was proposed to decompose hot-wire and pitot-probe measurements of freestream disturbances into the three Kovasznay modes (i.e., acoustic, entropy, and vorticity modes). By replacing the pitot-probe transfer function by Stainback and Wagner [33] with the DNS-predicted pitot-probe transfer function by Schilden and Schröder [40], the new combined modal decomposition method can yield rms values of modal amplitudes within a selected frequency band. In all, the joint effort of the specialists group has resulted in a significantly improved knowledge base pertaining to the nature and spectral contents of windtunnel freestream disturbances, with the purpose of quantifying the stochastic input to the receptivity process in a broadband disturbance environment of conventional, cold-flow hypersonic wind tunnels.…”
Section: Discussionmentioning
confidence: 99%
“…This modal decomposition method was based on total pressure and stagnation point heat flux fluctuations to decompose freestream disturbances via a sensitivity matrix containing transfer functions between the measured quantities and acoustic and entropy mode computed in DNS. Schilden and Schröder [40] showed that the proposed method is limited to a very low Strouhal number of the incident disturbances (i.e., the heat flux probe has to be very small to perceive essential postshock entropy modes). At this point, the hot wire is a promising alternative to the rather large SPP because it is basically a very small heat flux probe.…”
Section: B Kovasznay Modal Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…For supersonic flows, the code has been employed and validated for the flow past a cone and around a blunt stagnation point probe. 36,37 The DNS by the Technical University of Munich (TUM) are performed using the Navier Stokes Multi Block solver (NSMB). NSMB is an MPI-parallelized, finite-volume code for structured grids with a wide variety of numerical schemes and it has been extensively tested in studies of hypersonic flows.…”
Section: B Direct Numerical Simulationsmentioning
confidence: 99%
“…This modal decomposition method was based on total pressure and stagnation point heat flux fluctuations to decompose freestream disturbances via a sensitivity matrix containing transfer functions between the measured quantities and acoustic and entropy mode computed in DNS. Schilden and Schröder [40] showed that the proposed method is limited to very low Strouhal number of the incident disturbances, i.e., the heat flux probe has to be very small to perceive essential postshock entropy modes. At this point the hot-wire is a promising alternative to the rather large SPP since it is basically a very small heat flux probe.…”
Section: B Kovasznay Modal Decompositionmentioning
confidence: 99%